Motivation and preparation of women for leadership roles - Kopecká, Kristýna (2019)
This diploma thesis is focused on the topic of motivation and preparation of women for leadership roles, with a special focus on the preparation of female students at the University of Economics, Prague. The theoretical part of the thesis gives insight into the history of women in the workforce and on the Czech market, their preparation at world Universities or their preparation at the University of Economics, Prague. The practical part consists of two researches – one focused on students, the other focused on women in leadership roles. These two researches in the end provide an idea about the current preparation of female students for a leadership role, their motivation for such role and compare outcomes with the reality of female leaders.